The topoisomerase II poison clerocidin alkylates non-paired guanines of DNA: implications for irreversible stimulation of DNA cleavage - Gatto, Barbara (Oxford University Press, 2001)
Clerocidin, a diterpenoid with antibacterial and antitumor activity, stimulates in vitro DNA cleavage mediated by mammalian and bacterial topoisomerase (topo) II. Different from the classical topoisomerase poisons, clerocidin-stimulated breaks at guanines immediately preceding the sites of DNA cleavage are not resealed upon heat or salt treatment. To understand the mechanism of irreversible trapping of the topo II-cleavable complex, we have investigated the reactivity of clerocidin per se towards DNA. We show here that the drug is able to nick negatively supercoiled plasmids. DNA cleavage by clerocidin in enzyme-free medium is due to the ability of the drug to form covalent adducts with guanines. Indeed, clerocidin was able to specifically react with short oligonucleotides when the guanines were unpaired and exposed as in bulges or in the single-strand form. The clerocidin epoxy group attacks the nitrogen at position 7 of guanines, leading to strand scission at the modified site. Our findings also demonstrate that trapping of topoisomerases by clerocidin is specific for type II enzymes. The guanine-alkylating ability of clerocidin suggests an unprecedented mechanism of topo II poisoning, according to which the enzyme renders the drug reactive toward DNA by distorting the double-helical structure of the nucleic acid at the cleavage site.